PENGARUH TIPE KEPRIBADIAN DAN LINGKUNGAN KELUARGA TERHADAP KEMAMPUAN INTERAKSI SOSIAL MAHASISWA - Amma Ghifar Ibrahim; Bagus Haryono (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2022)
This study aims to explain the effect of introverted extrovert personality type on students' social interaction skills. The research sample was 121 students in one of the university in East Java. Data were obtained using a questionnaire with variable measurements using a Likert scale. The data analysis technique used multiple regression. The results showed that there was no influence of personality type on students' social interaction skills. Meanwhile, there is a significant positive effect of the family environment on students' social interaction skills. Based on the results of the R2 test of 36%, which means that students' social interaction skills can be explained by the variables of personality type and family environment.